THE ROLE OF INNOVATIONS AND STARTUPS IN ECONOMIC GROWTH: THE CASE OF UZBEKISTAN - Mashrapov Qudratillo; Mamadaliyev Jaxongir (TADQIQOTLAR, 2025)
This extended scientific article provides an in-depth analysis of the role of innovations and startups in the economic growth of the Republic of Uzbekistan. The study examines the formation of innovation policy, the stages of startup ecosystem development, and their impact on gross domestic product (GDP), employment, and national competitiveness using statistical and analytical methods. The research findings demonstrate that innovations and startups have become key drivers accelerating economic growth in Uzbekistan.